1994
DOI: 10.2190/mkd9-w05t-yj9y-81nm
|View full text |Cite
|
Sign up to set email alerts
|

Non-Speech Sound in Human-Computer Interaction: A Review and Design Guidelines

Abstract: Recent developments in computer technology make it possible to use sound more extensively in the computer interface than has hitherto been possible. This article describes research on uses of computer sound and suggests how sound might be used effectively by instructional and interface designers. After a review of some general principles of interface design and of basic research into auditory perception, the article examines two uses of sound Earcons, whose purpose is to inform the user about the state of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…While some multimedia research studies have suggested or inferred strategies for integrating sound generally, they offer few systematic design guidelines for incorporating sound-particularly music and sound effects-in ways that might improve learning (see for example Deatherage, 1972;Hereford & Winn, 1994;Lee & Owens, 2000;Najjar, 1998). According to Clark and Mayer (2003), more research is needed to determine whether sound might contribute more to learning than simply help reduce visual processing load when necessary.…”
mentioning
confidence: 99%
“…While some multimedia research studies have suggested or inferred strategies for integrating sound generally, they offer few systematic design guidelines for incorporating sound-particularly music and sound effects-in ways that might improve learning (see for example Deatherage, 1972;Hereford & Winn, 1994;Lee & Owens, 2000;Najjar, 1998). According to Clark and Mayer (2003), more research is needed to determine whether sound might contribute more to learning than simply help reduce visual processing load when necessary.…”
mentioning
confidence: 99%
“…Despite these recent advances in the fi eld, concrete and specifi c sonifi cation design guidelines that are grounded in literature and theory are still not generally available. While researchers have described guidelines for nonspeech auditory displays (Hereford and Winn, 1994;Watson and Kidd, 1994;Flowers, 2005;Edworthy and Hellier, 2006), these attempts have generally provided advice for particular instantiations of auditory displays as opposed to…”
Section: Design Considerations Formentioning
confidence: 99%
“…With the advent of ubiquitous digital technologies, high-fi delity sound samples have become increasingly easy and inexpensive to produce and implement (Hereford and Winn, 1994;Flowers, Buhman, and Turnage, 2005). Perhaps more important, however, an increasing awareness of the shortcomings and limitations of traditional visual interfaces has spurred research on sound as a viable mode of information display.…”
Section: Introductionmentioning
confidence: 99%
“…They can be produced using any systematic set of musical elements that can vary according to frequency, timbre or tempo in order to indicate hierarchy. Guidelines for their design have been suggested by Hereford and Winn [9].…”
Section: Earconsmentioning
confidence: 99%